Not Biting the Hand That Feeds You: How Perverted Accountability Affects the Ethical Leadership of Dutch Mayors. (2nd November 2019) - Karsten, Niels
Abstract : Dutch mayors are in the curious position that, by law, they are required to act against any integrity violations by their fellow political executives and municipal councilors. At the same time, they are fully accountable to the local council, and increasingly dependent on the political support of those they oversee for remaining in office and for their capacity to govern. Data collected from four focus groups and nine interviews indicate that this dependence has produced a precarious situation of "perverted accountability" in which mayors, because they perceive social and career risks, are more likely to refrain from assertive action against integrity violations than the accountability and ethical leadership literature suggests. Here, it is argued that there is an institutional aspect to such reluctance to be an effective moral leader that goes beyond Dutch mayors simply having weak personalities. The current study finds support for the unfashionable argument that accountability can be bad for democracy. It contributes to the study of ethical leadership by identifying perceived personal and positional risks as real-life impediments to ethical leadership and by drawing attention to the complexities of ethical leadership in the realm of politics.